Acute oral toxicity of Pereskia bleo and Pereskia grandifolia in mice - Sim, K.S.; Sri Nurestri, A.M.; Sinniah, S.K.; Kim, K.H.; Norhanom, A.W. (Medknow Publications, 2010)
Pereskia bleo and Pereskia grandifolia, belonging to the botanical family Cactaceae, have been traditionally used by the locals in Malaysia for treatment of various ailments. The current study reports the outcome of acute oral toxicity investigation of Pereskia bleo and Pereskia grandifolia, on ICR mice. No mortalities or evidence of adverse effects have been observed in ICR mice following acute oral administration at the highest dose of 2500 mg/ kg crude extracts of Pereskia bleo and Pereskia grandifolia. This is the first report on the acute oral toxicity of Pereskia bleo and Pereskia grandifolia and the findings of this study are in agreement with those of in vitro experiments and thus provide scientific validation on the use of the leaves of Pereskia bleo and Pereskia grandifolia.